A dominant negative zebrafish Ahr2 partially protects developing zebrafish from dioxin toxicity. - Kevin A Lanham; Amy L Prasch; Kasia M Weina; Richard E Peterson; Warren Heideman (PLoS ONE)
The toxicity by 2,3,7,8 tetrachlorodibenzo-p-dioxin (TCDD) is thought to be caused by activation of the aryl hydrocarbon receptor (AHR). However, our understanding of how AHR activation by TCDD leads to toxic effects is poor. Ideally we would like to manipulate AHR activity in specific tissues and at specific times. One route to this is expressing dominant negative AHRs (dnAHRs). This work describes the construction and characterization of dominant negative forms of the zebrafish Ahr2 in which the C-terminal transactivation domain was either removed, or replaced with the inhibitory domain from the Drosophila engrailed repressor protein. One of these dnAhr2s was selected for expression from the ubiquitously active e2fα promoter in transgenic zebrafish. We found that these transgenic zebrafish expressing dnAhr2 had reduced TCDD induction of the Ahr2 target gene cyp1a, as measured by 7-ethoxyresorufin-O-deethylase activity. Furthermore, the cardiotoxicity produced by TCDD, pericardial edema, heart malformation, and reduced blood flow, were all mitigated in the zebrafish expressing the dnAhr2. These results provide in vivo proof-of-principle results demonstrating the effectiveness of dnAHRs in manipulating AHR activity in vivo, and demonstrating that this approach can be a means for blocking TCDD toxicity.